INCOME INEQUALITY: EDUCATION AS THE PANACEA - Kusumaningsih, Nugraheni (Jurnal Kajian Ekonomi dan Keuangan, 2014)
The Indonesian government has already allocated 20 percent from its budget every year for education. Therefore, it's profound to know whether the budget spent on education is giving significant return. The paper aims to examine the rate of return to education, whether there's a disparity between rate of return to education between females and males, and whether education can help tighten the gap of income inequality which is a crucial issue these days facing emerging countries. This paper is using Mincer Equation as the model and Indonesian Family Life Survey (IFLS), a panel data from Indonesian households, finding the rate of return to education to be 7.5 percent. Interesting finding coming from return to education for females to be not different from males, given that return to education for females usually higher than males, though disparity tends to get smaller over time. In addition, it is found that education is not widening the gap of inequality though we can't say whether income equalizing process through education really occurs except for female case, it is income equalizing. This finding is crucial showing that the government should pay more focus in educating females as a means to tighten the income inequality gap.